Covering Former ISIS Fighters: A Framing Analysis of the Repatriation of Ex-ISIS in the Online Coverage of Kompas and Republika - Hamidah, Lilik; Nurhalizah, Mevy Eka (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2020)
This paper discusses how Kompas.com and Republika.co.id framed the coverage of the repatriation of ex-ISIS members to Indonesia. This study was a qualitative study using the approach of Robert N. Entman framing analysis model. The findings revealed that Kompas.com and Republika Online framed the return of the former ex-ISIS fighters to Indonesia differently in terms of the selection of news sources, legal analysis, and approval. Kompas.com tended to choose state officials to be a source to conduct analysis based on state law and reject repatriation of ex-ISIS. Meanwhile, Republika Online tended to select religious leaders to analyse based on Islamic law and allowed them to repatriate to this country. In other words, Kompas.com focused on the principle of humanism, while Republika Online more emphasised on Islam values and nationalism in their news coverage.